ANALISIS PROSEDUR PENERBITAN SURAT PERSETUJUAN PENGELUARAN BARANG (SPPB) PADA KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI TIPE MADYA PABEAN C MANADO - Maruru, Widya; Sondakh, Jullie; Rondonuwu, Sintje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
The one way to be able to control and supervise issuance of Approval Letter of Expenditure of Goods (SPPB) of import by carrying out the procedures and rules that apply. In the regulation of the Director General of Customs and Excise No. PER-16/BC/2016 concerning Hints Implementation Spending Goods Import For Used, explain about system work service Notice Import Goods (PIB) to on publishing Letter Approval Spending Goods (SPPB). Aim research this is for knowing procedure publishing Letter Objection Spending Goods (SPPB) on Oversight Office and Customs and Excise Type Madya Customs C Manado already corresponding or not yet corresponding with regulations director General of Customs and Excise No. PER-16 / BC / 2016. Research this use method research qualitatively. Results from research this that is procedure publishing Letter Approval Spending Goods (SPPB) already corresponding with rules director Jen deral Customs and Excise Number: PER -1 6 / BC / 2016. D iharapkan K antor Supervision and Customs and Excise Type Madya Customs C Manado continue improve quality in publishing Letter Approval Spending Goods (SPPB) imports, because now this so many goods imports coming in dae rah customs and need accuracy in p examination from stage importer fill and make Notice Import (PIB) to publishing Letter Approval Spending Goods (SPPB) so as not happen import prohibited goods sign in to in area customs and no reduce State revenue.Keywords : Procedures, rules, SPPB, import.